1998
DOI: 10.1103/physrevb.58.1550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ga/Si interdiffusion on optical and transport properties of GaN layers grown on Si(111) by molecular-beam epitaxy

Abstract: Optical and transport properties of wurtzite GaN layers, grown by plasma-assisted molecular-beam epitaxy on Si͑111͒ substrates, have been investigated. An emission at 3.455 eV, analyzed by continuous-wave and time-resolved luminescence in undoped and Si-doped GaN layers, is assigned to excitons bound to Si donors with an optical binding energy of 50 meV. A common origin of this peak, for undoped and Si-doped GaN, is backed by secondary-ion-mass spectroscopy that evidences a Si diffusion from the substrate into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 44 publications
(52 reference statements)
4
40
0
7
Order By: Relevance
“…13,14,15 However, the mutual solubility of Si and Al is high at the buffer layer temperature (eutectic point 577°C). Therefore AlN may exacerbate interdiffusion at the interface 6,16 which results in high unintentional doping levels in both the film and substrate. These drawbacks merit further investigation of alternative buffer layers.…”
mentioning
confidence: 99%
“…13,14,15 However, the mutual solubility of Si and Al is high at the buffer layer temperature (eutectic point 577°C). Therefore AlN may exacerbate interdiffusion at the interface 6,16 which results in high unintentional doping levels in both the film and substrate. These drawbacks merit further investigation of alternative buffer layers.…”
mentioning
confidence: 99%
“…The lower intensity and slight broadening exhibited by the A 1 ͑LO͒ mode in the annealed layer can be attributed to an increased density of free carriers due to the diffusion of Si donor atoms, which to a much lower degree also takes place in the crater-free regions. 3,13,14 In contrast, the Raman spectrum of the crater region is dramatically changed. No Raman signal of the GaN modes can be detected in these regions, which display a Raman spectrum dominated by a considerably broadened Si peak.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Si diffusion from the substrate 2,3 and the formation of an amorphous SiN x layer at the interface 2 contribute to degrade the epilayer quality. The insertion of an AlN buffer is widely used to avoid these problems and to accommodate lattice mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is consistent with the early work by Kurtin et al,14 who found that the surfaces of ionic crystals tend to be perfect due to their strong ionic nature. On the other hand, low-energy electron diffraction (LEED) and reflection high-energy electron diffraction (RHEED) were employed to study the surface reconstruction of molecular beam epitaxy (MBE)-grown GaN, 15,16 and clear diffraction patterns were observed, showing that a high-quality surface with low-density dangling bonds can be obtained. Although LEED and RHEED are not available in the MOCVD systems, the crystal quality of GaN grown by MOCVD is identified to be superior or at least comparable to GaN grown by MBE.…”
Section: Photoreflectance Study Of N-type Gan Epilayersmentioning
confidence: 99%